Solve by elimination method :2x +3y =4;3x - 2y = 6
Answers
Answer:
2x +3y =4----- (1)
3x - 2y = 6 -----(2)
Multiplying eq 1 by 3 and eq 2 by 2
6x+9y-12=0 ----(3)
6x-4y-12=0 ----(4)
Subtracting eq 4 from eq 3
6x+9y-12-6x+4y+12=0
5y=0
y=0
Substituting the value of y in eq 1
2x +3(0) =4
2x=4
x=2
Value of x=2 and y=0
Hope it helps<3
Answer:
x = 2, y = 0
Step-by-step explanation:
2x + 3y = 4 ... I
3x - 2y = 6 .....II
First we need to choose a variable. You can choose any, but it's better to choose y, as y has opposite signs in both equations, so we can simply add them
Now make the coefficients of the chosen variable same.
Multiply eqn. I by 2 and eqn. II by 3
2(2x + 3y = 4) => 4x + 6y = 8... III
3(3x - 2y = 6) => 9x - 6y = 18 ... IV
Add eqn. III and IV
On adding, 6y and -6y get cancelled, and we get
4x + 9x = 8 + 18
13x = 26
x = 2
Substitute x = 2 in eqn. I
2(2) + 3y = 4
4 + 3y = 4
3y = 0
y = 0
Solution set = {2, 0}
Hope this helps!